Informal settlements : a perpetual challenge? - Huchzermeyer, Marie; Karam, Aly (UCT Press eBooks, 2006)
This is an open, enlightening and useful book for scholars, activists, citizens and decision makers who consider that forced or market-driven evictions should stop and that the situation of slum dwellers must be improved, even beyond the limited Millennium Development Goals. – Professor Yves Cabannes, Development Planning Unit, University College London and Convenor, UN Advisory Group on Forced Evictions Addressing the housing problem has been one of the key concerns in post-apartheid South Africa, and the last two years have seen a major shift from the policy which was in place during the first ten years of democracy. The upgrading of informal settlements comes as a new addition to the revised housing policy, at a time when international bodies have prioritised the improvement of the lives of slum dwellers. The subject matter of this book is therefore highly topical, and is likely to be of interest to a wide audience within South Africa and elsewhere. – Professor Vanessa Watson, School of Architecture, Planning and Geomatics, University of Cape Town Everyone needs a safe place to live. Every family should have a secure home from which to pursue the adequate standard of living which, over twenty-five years ago, the Universal Declaration of Human Rights asserted was a fundamental entitlement of every man, woman and child on this planet. Over half a century later, the global community and national governments remain far short of this goal. Informal settlements have become a particular challenge. Upgrading the overall conditions for our urban poor is an urgent priority, since it is the key to the far more effective pursuit of many other of the Millennium Development Goals. I therefore commend this book as an important contribution, not just to theoretical debate, but to practical policy development and implementation, in South Africa and beyond. – The Most Reverend Njongonkulu Ndungane, Anglican Archbishop of Cape Town